2011 IEEE/WIC/ACM International Conferences on Web Intelligence and Intelligent Agent Technology 2011
DOI: 10.1109/wi-iat.2011.237
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Semi-automated Semantic Annotation Approach for Bootstrapping the Analysis of Large-Scale Web Service Networks

Abstract: Abstract-In recent years many methods have been proposed, which require semantic annotations of Web services as an input. Such methods include discovery, match-making, composition and execution of Web services in dynamic settings, just to mention few. At the same time automated Web service annotation approaches have been proposed for supporting application of former methods in settings where it is not feasible to provide the annotations manually. However, lack of effective automated evaluation frameworks has s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The effectiveness of the weighted network model in capturing and preserving the structural properties of underlying Web services network is already studied in [7,12]. The following definition defines how a weighted Web services network is transformed into a weighted label network.…”
Section: Definition 163 (Weighted Labeled Web Services Network) a Wmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of the weighted network model in capturing and preserving the structural properties of underlying Web services network is already studied in [7,12]. The following definition defines how a weighted Web services network is transformed into a weighted label network.…”
Section: Definition 163 (Weighted Labeled Web Services Network) a Wmentioning
confidence: 99%
“…They formalized the interaction between these two domains in terms of overlapping concepts used in annotation of input and output parameter of relevant Web services. Finally, Mokarizadeh et al [12] suggested a method for analyzing information diffusion between categories of data-centric Web services. The method operates on a Web services network constructed by linking interface descriptions of categorized Web services.…”
Section: Related Workmentioning
confidence: 99%
“…Since the annotated elements are in fact instances in the generated reference ontology, the instance matching process is used to find ontological relationships between those annotated elements. We employ a rule-based instance matching method that has already been described and evaluated in our previous work [13]. The matching method takes as input a pair of instances and produces a correspondence element.…”
Section: A Matching Inputs and Outputs Of Interface Descriptions Of mentioning
confidence: 99%
“…Every semantic node is further associated with category vector − → Q denoting the weight of the semantic node in different categories wrt its relative occurrence in the categories. The effectiveness of the semantic network model in capturing and preserving the structural properties of underlying Web services network is evaluated and proved in our previous work [13].…”
Section: Web Services Network Modelsmentioning
confidence: 99%
See 1 more Smart Citation